An investigation of toxicities and survival in Hispanic children and adolescents with ALL: Results from the Dana‐Farber Cancer Institute ALL Consortium protocol 05‐001. Issue 3 (1st November 2017) - Kahn, Justine M.; Cole, Peter D.; Blonquist, Traci M.; Stevenson, Kristen; Jin, Zhezhen; Barrera, Sergio; Davila, Randy; Roberts, Emily; Neuberg, Donna S.; Athale, Uma H.; Clavell, Luis A.; Laverdiere, Caroline; et al.
Abstract: Purpose: This study compared the relative incidence of treatment‐related toxicities and the event‐free and overall survival between Hispanic and non‐Hispanic children undergoing therapy for acute lymphoblastic leukemia (ALL) on Dana‐Farber Cancer Institute ALL Consortium protocol 05‐001. Patients and methods: Secondary analysis of prospectively collected data from a phase III multicenter study in children and adolescents of 1–18 years with previously untreated ALL. Results: Between 2005 and 2011, 794 eligible patients enrolled on DFCI 05‐001, 730 of whom were included in this analysis (19% [N = 150] Hispanic, 73% [N = 580] non‐Hispanic). Hispanic patients were more likely to be ≥10 years of age (32% vs. 24%, P  = 0.045) at diagnosis. Toxicity analyses revealed that Hispanic patients had significantly lower cumulative incidence of bone fracture ( P  < 0.001) and osteonecrosis (ON; P  = 0.047). In multivariable risk regression, the risk of ON was significantly lower in Hispanic patients ≥10 years (HR 0.23; P  = 0.006). Hispanic patients had significantly lower 5‐year event‐free survival (EFS) (79.4%; 95% CI: 71.6–85.2) and overall survival (OS) (89.2%; 95% CI: 82.7–93.4) than non‐Hispanic patients (EFS: 87.5%; 95% CI: 84.5–90.0, P  = 0.004; OS: 92.7%; 95% CI: 90.2–94.6, P  = 0.006). Exploratory analyses revealed differences between Hispanic and non‐Hispanic patients in the frequency of common variants in genes related to toxicity or ALL outcome. Conclusion: Hispanic children treated for ALL on DFCI 05‐001 had fewer bone‐related toxicities and inferior survival than non‐Hispanic patients. While disease biology is one explanatory variable for outcome disparities, these findings suggest that biologic and non‐biologic mechanisms affecting drug delivery and exposure in this population may be important contributing factors as well.